A Case of Anti-SAE1 Dermatomyositis. (4th March 2022) - de Vries, Max; Schreurs, Marco W. J.; Ahsmann, Els J. M.; Spee-Dropkova, Marcela; Karim, Faiz
Abstract : Introduction . Anti-SAE1 antibodies have a low prevalence in dermatomyositis patients. Case Description . A 61-year-old woman presented with progressive shortness of breath, arthralgia, heliotrope rash, Gottron's papules, and erythematous rash. She had an interstitial lung disease (ILD) with a significant decrease in lung function. There was no muscle involvement. Immunological laboratory test results showed strongly positive anti-SAE1 antibodies. Glucocorticoid treatment resulted in remission of dermatomyositis. Conclusion . Anti-SAE antibodies in dermatomyositis patients are closely linked to unique clinical features.